A Pt-Based Carbon-Free Cathode with Embedded Oxygen Nanoreservoirs: A Promising Approach for Oxygen Buffering to Aid Oxygen Reduction Reactions of PEMFCs - Yoyakki, Athira; Kumar, Sachin; Pandikassala, Ajmal; Jadhav, Swapnil D.; Vinod, C. P.; Kurungot, Sreekumar (ACS Catalysis, 2025)
For practical applications of proton exchange membrane fuel cells (PEMFCs), the system needs to be operated by employing air in the cathode instead of pure oxygen (O2). This makes it necessary to develop innovative electrode engineering solutions so that the system can function well even in oxygen-lean environments under the realistic working conditions of PEMFCs. Taking this into account, we introduce Pt/SiO2@CeO2-30%, an engineered electrocatalyst with potentially generated oxygen vacancies (Ov), which can immensely contribute toward the enhancement in the O2 availability in oxygen-lean conditions like the air feed conditions, allowing an effective control of the overpotential related to the oxygen reduction reactions (ORRs) at the electrode level. The meticulously crafted Pt-CeO2 interface serves as one of the appreciable structural attributes of the present catalyst, facilitating oxygen spillover toward the Pt environment, aided by the creation of the immense Ov along the nano CeO2 phase of the catalyst. In addition to the benefit of addressing the oxygen-lean conditions and overcoming the limitations of the state-of-the-art catalysts, usage of a noncarbonaceous support like SiO2 to house the Pt and CeO2 nanoparticles has been anticipated to lessen the corrosion problems, a major drawback associated with the carbon-based ORR catalysts. Apart from this, a significant contribution of SiO2 to the self-humidification of the ionomer interface plays a crucial role in enabling the MEA to work under low relative humidity conditions, which can be attributed to an additional benefit of the current composition of the catalyst. The catalyst demonstrated a promising ORR performance with a substantial improvement in H2-air feed circumstances and better corrosion resistance when tested with a membrane electrode assembly (MEA) in a single-cell configuration, illustrating the practical feasibility in a realistic system-level validation.
Keywords: carbon corrosion; carbon-free electrocatalyst; oxygen buffering; oxygen reductionreaction; oxygen spill over; protonexchange membrane fuel cell